2019
DOI: 10.4314/bcse.v33i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synthesized temperature on the assembly and properties of four lanthanide supramolecular frameworks

Abstract: Four new lanthanide coordination polymers, [H3O][Ln3(HPA)10(H2O)3·2H2O] (Ln = Pr for 1, Ln = Nd for 2), [Ln2(HPA)6(H2O)4·2H2O] (Ln = Sm for 3, Ln = Tb for 4) (HHPA =3-(4-hydroxyphenyl)propanoic acid), were successfully synthesized and characterized. 1 and 2 are isostructural and have 1D metal chain structure, while 3 and 4 show 0D network with binuclear subunits. The results indicated that the effect of reaction temperature can modulate the final structures. The HPA ligands adopt bidentate chelating and triden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Nitrous oxide produced by treating animal manure slurry is another important source of GHGs. Previous experimental results have shown the effect of the slurry temperature on the global emissions of N 2 O [50] and concluded that an increase in temperature could accelerate N 2 O production in the temperature range of 15-35 • C, while reductions in emissions are practically non-existent at lower temperature values (Figure 4).…”
Section: • N 2 O Emissionsmentioning
confidence: 92%
“…Nitrous oxide produced by treating animal manure slurry is another important source of GHGs. Previous experimental results have shown the effect of the slurry temperature on the global emissions of N 2 O [50] and concluded that an increase in temperature could accelerate N 2 O production in the temperature range of 15-35 • C, while reductions in emissions are practically non-existent at lower temperature values (Figure 4).…”
Section: • N 2 O Emissionsmentioning
confidence: 92%
“…[84] Pyrolysis at 1600 °C created Ta 4 HfC 5 nanocrystallites of %21 nm, encapsulated by an amorphous C layer. [84] A solution-based process can mix the starting materials at a fine scale. Therefore, synthesis temperature can be reduced since long-distance atomic diffusion is not demanded.…”
Section: Transition Metal Carbidesmentioning
confidence: 99%
“…[50b,51] Solid-solution silicon carbide Atomic-level homogeneity, higher yield, lower ceramic conversion temperature than for pure SiC, inhibited β-SiC crystal growth, and improved densification 84%-89% ceramic yield, [4b,62] ceramic conversion completes at 800 °C. [62] Transition metal carbides Atomic-level homogeneity, lower ceramic conversion temperature than for pure SiC, pseudopolymer-derived carbide when using simple organic species, residual oxygen, and improved ceramic yield; C preform, carbide particles, or precursor infiltration may be used 45-75% yield, [89] 1.6 wt% residual C, [89] polymer conversion to amorphous carbides at <900 °C, [69,70] carbide crystallization at >1000 °C, [71,77,80,81,[83][84][85]93,97] crystal size varies from single nanometer to a few hundred nanometers. [70,89,97,98] Borides Constrained grain growth, metal sources can be oxide or salt based 86-90% yield, [101,102] pyrolysis at >1400 °C leads to borides.…”
Section: Materials Characteristics Specificsmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, o complexo ATG5-ATG12-ATG16L funciona como uma enzima semelhante a E3, determinando o local de lipidação de LC3 (18). A LC3 II também interage diretamente com a sequestossomo 1 (Sqstm1/p62), proteína que marca quem deve ser envolto pelo autofagossoma e degradado por autofagia (7,11,12,(19)(20)(21)(22). As ações dos microtúbulos garantem o transporte preciso do autofagossomo ao lisossoma para fusão (23).…”
Section: Via Da Autofagiaunclassified